Osteogenesis from Dental Pulp Derived Stem Cells: A Novel Conditioned Medium Including Melatonin within a Mixture of Hyaluronic, Butyric, and Retinoic Acids - Margherita Maioli; Valentina Basoli; Sara Santaniello; Sara Cruciani; Alessandro Palmerio Delitala; Roberto Pinna; Egle Milia; Regina Grillari-Voglauer; Vania Fontani; Salvatore Rinaldi; Roberta Muggironi; Gianfranco Pigliaru; et al. (Stem Cells International)
Human dental pulp stem cells (hDPSCs) have shown relevant potential for cell therapy in the orthopedic and odontoiatric fields. The optimization of their osteogenic potential is currently a major challenge. Vascular endothelial growth factor A (VEGF A) has been recently reported to act as a major conductor of osteogenesis in vitro and in vivo. Here, we attempted to prime endogenous VEGF A expression without the need for viral vector mediated gene transfer technologies. We show that hDPSCs exposure to a mixture of hyaluronic, butyric, and retinoic acids (HA + BU + RA) induced the transcription of a gene program of osteogenesis and the acquirement of an osteogenic lineage. Such response was also elicited by cell exposure to melatonin, a pleiotropic agent that recently emerged as a remarkable osteogenic inducer. Interestingly, the commitment to the osteogenic fate was synergistically enhanced by the combinatorial exposure to a conditioned medium containing both melatonin and HA + BU + RA. These in vitro results suggest that in vivo osteogenesis might be improved and further studies are needed.